2023
DOI: 10.3390/ph16060869
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Potentially Inappropriate Medication Use among Older Adults

Abstract: Background: Use of potentially inappropriate medication (PIMs) is a prominent concern that leads to significant medication-related issues among older adults. Notably, older women tend to utilize more medicines than men; older women frequently take more drugs. In addition, some evidence suggests that prescription PIMs vary by gender. This study examines the gender-based variation in prescribing PIM among older adults in Saudi Arabia. Methods: A cross-sectional retrospective analysis of electronic medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…Diuretics can affect age-related homeostasis, resulting in a greater risk of orthostatic hypotension, falls and electrolyte imbalance [ 149 ]. On the other hand, age, sex, ADL, clinical frailty, comorbidities, a history of falls within the past 12 months and cognitive function were not correlated with exposure to >1 criterion of DRPs, which is in contrast with preceding studies [ 38 , 150 , 151 , 152 , 153 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Diuretics can affect age-related homeostasis, resulting in a greater risk of orthostatic hypotension, falls and electrolyte imbalance [ 149 ]. On the other hand, age, sex, ADL, clinical frailty, comorbidities, a history of falls within the past 12 months and cognitive function were not correlated with exposure to >1 criterion of DRPs, which is in contrast with preceding studies [ 38 , 150 , 151 , 152 , 153 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Other evidence confirmed that also older women tend to utilize more medicines than men. In addition, some studies suggested that prescription of potentially inappropriate medications vary by gender ( Alwhaibi and Balkhi, 2023 ).…”
Section: Differences Between Women and Men In The Use Of Medicinesmentioning
confidence: 99%